Impact of Migration on Entrepreneurial Activity Development - Kolesnik, Nadezhda; Dvouletý, Ondřej; Válek, Lukáš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
The Master Thesis aims to investigate the relationship between migration and entrepreneurial activity development. The sample consists of 21 countries within the year range of 2006-2019. Data is formed as a panel dataset and obtained from different databases. Entrepreneurial activity is reflected by the rate of a newly registered business, new business ownership rate, and established business ownership rate, depending on the model. A model is developed for each variable following the Robust Fixed Effects approach. Migration is found to be positively related to the development of entrepreneurial activities. The thesis also finds other variables influencing entrepreneurial activities, such as GDP per capita (positive), fixed broadband subscription (positive), and control of corruption (positive). The thesis supports the hypothesis that immigrants from Asia are more prone to engage in entrepreneurial activities. It also finds certain relations between immigrant stock from other regions and the development of entrepreneurial activities.
Vedoucí práce: Ondřej Dvouletý
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses